Identification of plant disease images via a squeeze‐and‐excitation MobileNet model and twice transfer learning - Chen, Junde; Zhang, Defu; Suzauddola, Md; Nanehkaran, Yaser Ahangari; Sun, Yuandong (IET image processing, 2021)
Crop diseases have a devastating effect on agricultural production, and serious diseases can lead to harvest failure entirely. Recent developments in deep learning have greatly improved the accuracy of image identification. In this study, we investigated the transfer learning of deep convolutional neural networks and modified the network structure to improve the learning capability of plant lesion characteristics. The MobileNet with squeeze‐and‐excitation (SE) block was selected in our approach. Integrating the merits of both, the pre‐trained MobileNet and SE block were fused to form a new network, which we termed the SE‐MobileNet, and was used to identify the plant diseases. In particular, the transfer learning was performed twice to obtain the optimum model. The first phase trained the model for the extended layers while the bottom convolution layers were frozen with the pre‐trained weights on ImageNet; by loading the model trained in the first phase, the second phase retrained the model using the target dataset. The proposed procedure provides a significant increase in efficiency relative to other state‐of‐the‐art methods. It reaches an average accuracy of 99.78% in the public dataset with clear backdrops. Even under multiple classes and heterogeneous background conditions, the average accuracy realises 99.33% for identifying the rice disease types. The experimental findings show the feasibility and effectiveness of the proposed procedure.